Peran Guru Pendidikan Agama Katolik dalam Mengatasi Perilaku Antisosial pada Peserta Didik di SMP St. Antonius Bangun Mulia - Sembiring, Mimpin; Sembiring, Beny Papias (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Antisocial behavior is an action that harms others. At the junior high school level, anti-social behavior that appears to be carried out by students in the form of: bullying, not caring when their friends cry and laugh when they are punished and disturbing their friends during prayer. To overcome anti-social behavior in students, the existence of a PAK teacher is the right solution to overcome this behavior through its role, namely; as a motivator, learning manager, facilitator, role model and mentor. This study aims to overcome anti-social behavior in students through the role of PAK teachers. This research uses a qualitative approach with observation, interview, and documentation techniques. Based on the results of the study, the Catholic Religious Education (PAK) Teacher appears to have been effective in playing his role in overcoming anti-social behavior in students at SMP ST. Antonius Bangun Mulia Junior High School. Through his role, the Catholic Religious Education teacher has increased students' learning motivation, attracted students' interest in learning through learning management, provided various media to make it easier for students to understand the subject matter, became a model for students' behavior, and guided and directed students to have good attitudes and behavior.